Lilo's Psychosocial Development in Disney's Lilo & Stitch (2025): An Eriksonian Perspective - Fernanda Dimas Renaldi; Mufida Nadira Yuni Pureka; Indah Puspitasari (Jurnal Langua, 2026)
This study aims to analyze Lilo's psychosocial development in the movie Lilo & Stitch (2025) based on Erik Erikson's psychosocial development theory. Despite numerous studies applying Erikson's theory, little attention has been paid to how family attachment and cultural values interact to facilitate children's psychological recovery in contemporary live-action movies. This study employed a descriptive qualitative approach using content analysis. Data were collected through repeated observation of the movie, identification and coding of relevant scenes and dialogues, and classification based on Erikson's psychosocial development stages. The findings reveal that Lilo represents six of Erikson's eight psychosocial stages, with Identity versus Role Confusion emerging as the most dominant stage, followed by Trust versus Mistrust and Industry versus Inferiority. The analysis further demonstrates that parental loss, social rejection, and emotional relationships with Nani and Stitch significantly influence Lilo's psychosocial development. At the same time, the Hawaiian cultural philosophy of ohana serves as a protective framework that supports emotional recovery and identity formation. This study contributes to literary psychology by demonstrating that integrating family attachment and the cultural value of ohana enriches Erikson's psychosocial framework for interpreting children's psychological development in contemporary live-action movies.